Bigger Matters? Exploring the Mediating Effect of Firm Size on ESG Disclosure and Firm Value - Yulianti, Vista; Djatnicka, Erlina (Journal of Applied Accounting and Taxation, 2025)
This research investigates the effect of Environmental, Social, and Governance (ESG) disclosure on firm value with firm size as a mediating variable. The study is motivated by the growing importance of ESG initiatives in attracting investors, strengthening stakeholder trust, and promoting sustainable growth, particularly in developing markets such as Indonesia. The research adopts a quantitative approach using secondary data from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. ESG disclosure was measured through content analysis of sustainability reports, firm value was proxied by Tobin’s Q, and firm size was assessed using the natural logarithm of total assets. Data analysis employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and mediated relationships among variables. The results indicate that ESG disclosure significantly enhances firm value, supporting the argument that transparent sustainability practices reduce information asymmetry and strengthen market confidence. Furthermore, ESG disclosure was found to have a positive and significant effect on firm size, suggesting that firms with robust ESG practices tend to expand more rapidly and attract greater resources. Firm size also positively influences firm value, confirming its role as a strategic advantage. Mediation analysis reveals that firm size partially mediates the relationship between ESG disclosure and firm value, indicating that ESG disclosure affects valuation both directly and indirectly through organizational growth. In conclusion, the findings underscore the dual role of ESG disclosure as a direct driver of firm value and an indirect enhancer through firm size. For managers, this emphasizes the strategic importance of ESG initiatives not only as compliance measures but as growth enablers and value-creation mechanisms. The study provides important insights for regulators, investors, and corporate leaders in Indonesia, highlighting the need to strengthen ESG reporting standards and encourage firms to integrate sustainability into their core strategies to enhance competitiveness and long-term value.